2019
DOI: 10.1016/j.vaccine.2019.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric, cognitive, and schooling benefits of measles vaccination: Longitudinal cohort analysis in Ethiopia, India, and Vietnam

Abstract: Objective To estimate the associations between measles vaccination and child anthropometry, cognition, and schooling outcomes in Ethiopia, India, and Vietnam. Methods Longitudinal survey data from Young Lives were used to compare outcomes at ages 7–8 and 11–12 years between children who reported receipt or non-receipt of measles vaccine at 6–18 months-of-life ( n = ∼2000/country). Z-scores of height-for-age (HAZ), BMI-for-age (BMIZ), weight-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 52 publications
3
43
0
1
Order By: Relevance
“…80 During the present decade, researchers have utilized and expanded this framework across several dimensions and country contexts. 76,77,[81][82][83][84][85] A new online database called the Value of Immunization Compendium Evidence (VoICE), created and maintained by the International Vaccine Access Center at the Johns Hopkins University, Bloomberg School of Public Health, now tracks research on the broader benefits of vaccines on health, educational, economic, and equity outcomes worldwide. 86 The Immunization Economics community of research and practice compiles similar and related information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…80 During the present decade, researchers have utilized and expanded this framework across several dimensions and country contexts. 76,77,[81][82][83][84][85] A new online database called the Value of Immunization Compendium Evidence (VoICE), created and maintained by the International Vaccine Access Center at the Johns Hopkins University, Bloomberg School of Public Health, now tracks research on the broader benefits of vaccines on health, educational, economic, and equity outcomes worldwide. 86 The Immunization Economics community of research and practice compiles similar and related information.…”
Section: Discussionmentioning
confidence: 99%
“…70 A recent longitudinal study of approximately 2,000 children each in Ethiopia, India, and Vietnam has linked measles vaccination at ages 6-18 months of life with 0.1-0.2 higher anthropometric z-scores, 1.7-4.5 percentage points higher scores on standardized cognition tests, and 0.2-0.3 additional schooling grades at ages 7-8 and 11-12 years. 71 The vaccine has also been associated with 0.2 more schooling grade attainment among South African children and 7.4% higher school enrollment rate among children in Bangladesh. 72,73 Similar growth, cognition, and schooling benefits have been observed among Haemophilus influenzae type B (Hib) vaccinated children in India, 74,75 and fully vaccinated children in the Philippines.…”
Section: Economic Equity and Global Health Benefits Of Vaccinesmentioning
confidence: 99%
“…Immunization is a proven tool for controlling and eliminating life-threatening infectious disease which prevent 2-3 million under-five deaths annually. Provision of measles vaccine can support cognitive gain, school-grade attainment, decrease malnutrition, economic consequence after childhood and also prevent severe pneumonia and diarrhea [67,68] We found regional variation for immunization coverage among 12-23 month children lowest prevalence was observed from Afar region 12.0 % (95% CI: 10.0, 13.0) were evidences showed that access to health facilities is very low, 82.12% of population resides in rural and pastoralist due to that and other reasons under five mortality is highest in Afar region comparing other eight regionals states which is (125 per 1000 live birth) high percent of death can be prevented simply providing immunization services children living hard-to-reach area [27,69]. Somali region is next to Afar region where immunization coverage is low and 37.0% (95% CI: 33.0%, 41.0%).…”
Section: Publication Biasmentioning
confidence: 99%
“…13–16 To our knowledge, only three studies looked at the effect of vaccination on children’s cognitive development. 17–19 Bloom et al , using cohort data from the Philippines (1983–1994), found that receiving at least one vaccination of each of the BCG vaccine against tuberculosis, the diphtheria-tetanus–pertussis vaccine (DTP), the oral polio vaccine (OPV) and the measles-containing vaccine (MCV) by age 2 raised intelligence tests scores at age 11 by about half an SD. 17 However, this study was based on a relatively small number of children.…”
Section: Introductionmentioning
confidence: 99%
“…Two other studies using cohort data from Ethiopia, India and Vietnam found positive effects of the measles and haemophilus influenzae type b vaccines on children’s cognitive test scores. 18 19 Given the absence of experimental evidence and differences in underlying socioeconomic conditions, schooling quality and burden of VPDs, replicating these findings for different vaccines and in other contexts is crucial.…”
Section: Introductionmentioning
confidence: 99%